Biotechnological applications of Listeria's sophisticated infection strategies - Barbuddhe, Sukhadeo (Blackwell Publishing Ltd, 2008)
Listeria monocytogenes is a Gram‐positive bacterium that is able to survive both in the environment and to invade and multiply within eukaryotic cells. Currently L. monocytogenes represents one of the most well‐studied and characterized microorganisms in bacterial pathogenesis. A hallmark of L. monocytogenes virulence is its ability to breach bodily barriers such as the intestinal epithelium, the blood–brain barrier as well as the placental barrier to cause severe systemic disease. Curiously, this theme is repeated at the level of the interaction between the individual cell and the bacterium where its virulence factors contribute to the ability of the bacteria to breach cellular barriers. L. monocytogenes is a model to study metabolic requirements of bacteria growing in an intracellular environment, modulation of signalling pathways in the infected cell and interactions with cellular defences involving innate and adaptive immunity. Technical advances such as the creation of LISTERIA‐susceptible mouse strains, had added interest in the study of the natural pathogenesis of the disease via oral infection. The use of attenuated strains of L. monocytogenes as vaccines has gained considerable interest because they can be used to express heterologous antigens as well as to somatically deliver recombinant DNA to eukaryotic cells. A novel vaccine concept, the use of non‐viable but metabolically active bacteria to induced immunoprotective responses, has been developed with L. monocytogenes. In this mini‐review, we review the strategies used by L. monocytogenes to subvert the cellular functions at different stages of the infection cycle in the host and examine how these properties are being exploited in biotechnological and clinical applications.